On the Boundedness and the Stability Results for the Solutions of Certain Third Order Non-Linear Differential Equations - Ogundare, B. S. (2014)
In this paper, we show the asymptotic stability of the trivial solution x = 0 for p = 0 and the boundedness as well as the ultimate boundedness result for p ≠ 0 with the use of a single complete Lyapunov function. The results obtained here improve on the results already obtained for this class of third order nonlinear differential equations.